Sebaceous carcinoma of the trunk and extremities: Epidemiology and treatment patterns in the United StatesCapsule Summary - Miles Grunvald, MD; Rachel Chang, BS; Samantha Terranella, MD; Ethan Ritz, MS; Parul Kathuria Goyal, MD; Cristina O'Donoghue, MD, MPH (Elsevier, 2024)
Background: Sebaceous carcinoma is a rare cancer, and little is known about its current epidemiology and treatment. This is particularly true for sebaceous carcinomas of the trunk and extremities. Objective: We present a database analysis of sebaceous carcinoma cases to further delineate demographics, location, tumor characteristics, and treatment modalities among patients diagnosed with these tumors. Methods: The National Cancer Database was queried for cases of sebaceous carcinoma between 2004 and 2016. 3211 cases were analyzed for descriptive and comparative statistics. Results: Twenty-six percent of sebaceous carcinomas were found on the trunk and extremities. Tumors on the trunk and extremities were more likely to be larger than tumors on the head and neck, with 8% being greater than 50 mm (P < .001). Tumors on the trunk and extremities were more likely to be well differentiated (P < .001) and have fewer lymph node metastases (P < .001). Surgery was the primary treatment modality for tumors, followed by radiotherapy and rarely chemotherapy. Conclusions: Sebaceous cancer is a poorly understood entity. We demonstrated that trunk and extremity tumors tend to be larger and more differentiated than those of the head and neck. Treatment practices are varied at this time, but surgery is the primary modality.